FOREIGN EXPERIENCE ON TRANSPORT AND LOGISTICS CLUSTER AND ITS APPLICATION IN UZBEKISTAN - Karrieva Yakutxan Karimovna (Scholar Express Journals, 2022)
In this article has been described in detail the work of the authors on the transport and logistics cluster in Uzbekistan and the practice of applying foreign experience in organizing their status. Also, the experience of transport and logistics clusters in developed countries is analyzed. In particular, a comparative analysis of the experience of the transport and logistics cluster in countries such as Finland, Japan, Russia, Kazakhstan and a number of recommendations for its application in Uzbekistan
Keywords: Cluster; transport; logistics; strategy